The Effect of Transcutaneous Vagus Nerve Stimulation in Patients with Polymyalgia Rheumatica - Jacob Venborg; Anne-Marie Wegeberg; Salome Kristensen; Birgitte Brock; Christina Brock; Mogens Pfeiffer-Jensen (MDPI AG, 2021)
(1) Polymyalgia rheumatica (PMR) is an inflammatory disease characterised by pain, morning stiffness, and reduced quality of life. Recently, vagus nerve stimulation (VNS) was shown to have anti-inflammatory effects. We aimed to examine the effect of transcutaneous VNS (t-VNS) on PMR. (2) Fifteen treatment-naïve PMR patients completed the study. Patients underwent a 5-day protocol, receiving 2 min of t-VNS stimulation bilaterally on the neck, three times daily. Cardiac vagal tone (CVT) measured on a linear vagal scale (LVS), blood pressure, heart rate, patient-reported outcome, and biochemical changes were assessed. (3) t-VNS induced a 22% increase in CVT at 20 min after initial stimulations compared with baseline (3.4 ± 2.2 LVS vs. 4.1 ± 2.9 LVS, p = 0.02) and was accompanied by a 4 BPM reduction in heart rate (73 ± 11 BPM vs. 69 ± 9, p < 0.01). No long-term effects were observed. Furthermore, t-VNS induced a 14% reduction in the VAS score for the hips at day 5 compared with the baseline (5.1 ± 2.8 vs. 4.4 ± 2.8, p = 0.04). No changes in CRP or proinflammatory analytes were observed. (4) t-VNS modulates the autonomic nervous system in patients with PMR, but further investigation of t-VNS in PMR patients is warranted.